Synthesis and electron-transport properties of a stable antiaromatic NiII norcorrole with the smallest meso-substituent. Issue 41 (13th October 2020) - Ukai, Shusaku; Koo, Yun Hee; Fukui, Norihito; Seki, Shu; Shinokubo, Hiroshi
Abstract : A stable and antiaromatic norcorrole Ni II complex has been synthesized with a small substituent, which exhibited good electron-transporting ability. Abstract : meso -Dimethylnorcorrole Ni II complex exhibited enough stability under ambient conditions despite the distinct antiaromaticity. The small methyl substituents realized a dense and long-range π-stacking in its solid state, which resulted in the superior electron-transporting ability to previously reported Ni II norcorroles.